Assessment of Rational Medicines Prescribing in Healthcare Facilities in Four Regions of Tanzania - Irunde, Henry; Minzi, Omary; Moshiro, Candida (Journal of Pharmacy Practice and Community Medicine)
Objective: The purpose of the study was to measure rational medicines prescribing in healthcare facilities from selected regions in Tanzania with focus on WHO/INRUD core medicines use indicators. Methods: The study is across-sectional and a total 2067 prescriptions were collated and studied from 67 health care facilities in four regions of Tanzania. WHO/INRUD core medicines use indicators were employed and these are; proportions of encounters with an injection prescription, % of prescriptions with an antibiotic, polypharmacy, use of generic name and medicines prescribed from National Essential Medicines List was determined. Collected data were analysed using the Statistical Package for Social Sciences (SPSS) version 16.0, SPSS, Inc; Chicago, USA. Index of Rational Drug Prescribing (IRDP) was used to rank facilities to their level of rational medicines prescribing. Results: The proportion of prescriptions with injections was found to be 18.1% while that containing antibiotics was 67.7% and the average number of medicines per prescription was 2.3. The proportion of medicines prescribed by generic was 95.7%while one that contained medicines in line with the National Essential Medicines List was 96.7%. The overall IRDP for the current study was 3.81with optimal level of 5. Kilimanjaro region scored highest IRDP (3.35) while Mbeya region scored the least (IRDP of 3.11). Rural healthcare facilities scored low IRDP (3.25) while for urban facilities IRDP was higher (3.42). IRDP for public healthcare facilities was higher (3.65) than for private facilities (3.02). Conclusion: Rational drug prescribing in Tanzania is not yet optimal leading to over-prescribing of antibiotics and injections.
Keywords: Rational Prescribing; Essential Medicines; Inappropriate Use; Healthcare Facilities; Tanzania